Islamic Financing Products and Instruments: A Thematic Review - Shinkafi, Akilu Aliyu; Ali, Nor Aini (Online Journal of Research in Islamic Studies, 2018)
Financing products are the most suggestive and thus important determinants and contribute a lot toward the survival or otherwise of Islamic financing institution. Of note, the aforementioned also contribute a large segment in an effort to promote the economic development of the human society. Yet, not much has been done to bind the effort of these contemporary scholars and link it on the subject. The central point of this work is to develop a thematic review on an effort of contemporary scholars on Islamic financing products with a view to bind the recent works together for effective guide and referral for the future research on the subject. Findings reveal Musharakah, Mudarabah, Murabahah, Ijarah, Sukuk, Qard al-Hassan, and Istisna` product are more popular among the recent accessible literatures. This is likely due to their potential alternative in the Islamic financial institutions, speed in developing economy, and their functional role in deriving benefit and attraction of client than others. The result further identified some of the Islamic financing products that receive partial attention by the present-day scholars, these include Kafala, Bay al-Inah and Ijarah thummal Bay.